“Teddy Bear Hospital Project” school visits improve pre-clerkship students’ comfort explaining medical concepts to children - Kis, Hannah; Endres, Kaitlin; Karwowska, Anna; Harrison, Megan; Lau, Stephanie; Lemire, Olivia; Zucker, Marc (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Implication StatementThe “Teddy Bear Hospital Project” (TBHP) is a low cost, international initiative aimed at reducing children’s fears associated with healthcare visits by modelling these interactions using teddy bears. The University of Ottawa program had the additional objective of assessing whether TBHP increased pre-clerkship medical students’ comfort communicating medical concepts to children. Our student volunteers reported a statistically significant increase in their comfort communicating medical topics to young children and all volunteers would recommend TBHP to a colleague interested in pursuing family medicine or pediatrics. Our program could also be easily replicated by Pediatric Interest Groups at other Canadian medical schools.